5.31. Rozwiąż dany układ równań metodą podstawiania. a) b) (x – 3)(y + 1) = xy – 5, \qquad (x + 1)(y – 3) = 7 + x(y – 5) (2x – y)(y + 5) = y(2x – y – 4), \qquad 3(8x – y) = 2(11y – w) (1x – y) (x-y)(x+2)-1\\ (x-y)\\ 2x-3y\\ 2 matrix = x+y 6 3(x-1)(x+3)-2(y+1)(y+2\\ y-1 4 = x 2 -1 x+3)-2(y+1)(y+2)+2y^ 2 =3(x^ 2 -y) x+2)=x(x-y)+4 c) 2x + 1 8x – 11 x+y A 6y – 5x B D x – 2y y + 2 2x – 3y + 1 d)

 5.31. Rozwiąż dany układ równań metodą podstawiania. a) b) (x – 3)(y + 1) = xy – 5, \qquad (x + 1)(y – 3) = 7 + x(y – 5) (2x – y)(y + 5) = y(2x – y – 4), \qquad 3(8x – y) = 2(11y – w) (1x – y) (x-y)(x+2)-1\\ (x-y)\\ 2x-3y\\ 2 matrix = x+y 6 3(x-1)(x+3)-2(y+1)(y+2\\ y-1 4 = x 2 -1 x+3)-2(y+1)(y+2)+2y^ 2 =3(x^ 2 -y) x+2)=x(x-y)+4 c) 2x + 1 8x – 11 x+y A 6y – 5x B D x – 2y y + 2 2x – 3y + 1 d)